2016
DOI: 10.1097/mrr.0000000000000168
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of working from a freestanding position as a case manager when supporting clients in the Swedish welfare system

Abstract: The Swedish state uses a case management function known as Personligt Ombud (PO). The role as PO differs from the traditional professional roles. It has a freestanding position in the welfare system. The aim of this study was to investigate POs' experiences of working from a freestanding position when supporting clients. Telephone interviews were conducted with 22 POs across Sweden. The interviews were recorded, transcribed, and analyzed by latent qualitative content analysis. The findings were reflected in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Ten studies met the inclusion criteria for this qualitative systematic review: Bamford et al (2014); Eack, Greeno, Christian-Michaels, Dennis, and Anderson, (2009); Gustafsson, Kristensson, Holst, Willman, and Bohman (2013); Iliffe et al (2011); Klockmo and Marnetoft (2016); Kolind, Vanderplasschen, and De Maeyer (2009); Moise and Mulhall (2016); O’Donnell (2007); Sandberg, Jakobsson, Midlöv, and Kristensson (2014); and You et al (2016). These studies were all published between 2007 and 2016.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies met the inclusion criteria for this qualitative systematic review: Bamford et al (2014); Eack, Greeno, Christian-Michaels, Dennis, and Anderson, (2009); Gustafsson, Kristensson, Holst, Willman, and Bohman (2013); Iliffe et al (2011); Klockmo and Marnetoft (2016); Kolind, Vanderplasschen, and De Maeyer (2009); Moise and Mulhall (2016); O’Donnell (2007); Sandberg, Jakobsson, Midlöv, and Kristensson (2014); and You et al (2016). These studies were all published between 2007 and 2016.…”
Section: Resultsmentioning
confidence: 99%
“…You et al (2016) observed that case managers in general had to deal with multiple complex tasks to meet clients’ needs. Case managers in Klockmo and Marnetoft (2016) said that they experienced demanding activities under tight deadlines: “It [case management] requires the ability to work independently, a high degree of self-confidence, the ability to listen to the client, and balance this with the authorities’ framework while not succumbing to exhaustion or burnout” (p. 128). Finally, some studies reported that unfamiliar roles make the work more challenging: “Adherence to these diverse conditions, both as an individual and as a team member, challenged their [case managers’] current professional identity” (Gustafsson et al, 2013, p. 7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations